Solid Waste Management Scenario and the Impacts of the Absence of Selective Collection in Conceição do Araguaia, Southeast of Pará (Research, Society and Development, 2022)
The research analyzed the main issues about the management of solid waste in the municipality of Conceição do Araguaia, and verified the problems related to the absence of selective collection. Aiming to present the Araguaiana community, the due care that must occur in the handling and disposal of solid waste, seeking to follow the protocols provided for in the National Solid Waste Policy, Law 12.305/2010. The development of the project was carried out in three stages. In Stage I, a bibliographic survey of the main guidelines and scientific information that address the issue of solid waste in the environment was carried out. Subsequently, information was collected through a virtual questionnaire. The selected data from the sample expose doubts that were presented by individuals who were willing to answer the questionnaire, assembling the environmental conceptions of part of the municipality's community. The project showed a positive percentage of 85.1% of people who are aware of what selective collection is, however, it reports only 26.7% as a percentage referring to individuals who carry out the separation of solid waste in their homes. When making a comparison between the management of the municipality, together with the actions of the population, the research concluded negligence of both parties in relation to the management of solid waste. Therefore, through this information, posters and pamphlets were prepared for dissemination on social networks and public environments, seeking to sensitize the community and expose the duties of government officials and the population in general.